Sulfuric Acid-Promoted Oxidation of Benzylic Alcohols to Aromatic Aldehydes in Dimethyl Sulfoxide: An Efficient Metal-Free Oxidation Approach - Sheikhi, Ehsan; Adib, Mehdi; Karajabad, Morteza Akherati; Gohari, Seyed Jamal Addin (Synlett, 2018)
An efficient metal-free oxidation of benzylic alcohols to aromatic aldehydes is described. Heating a solution of the benzylic alcohol in DMSO in the presence of H2SO4 afforded the corresponding aldehyde in excellent yield. This oxidation reaction, which proceeds with a short reaction time and no side products, is akin to the Pfitzner–Moffatt oxidation, but without the need for N,N′-dicyclohexylcarbodiimide.
Keywords: benzylic alcohols; aromatic aldehydes; sulfuric acid; dimethyl sulfoxide; oxidation